ANALYZING THE EFFECT OF BRAND EQUITY AND VISUAL MERCHANDISING ON CONSUMER PURCHASE DECISION AT GIORDANO MANADO TOWN SQUARE - Sambuaga, Resa .; Kindangen, Paulus .; Tielung, Maria V.J (Jurnal EMBA : Jurnal Riset Ekonomi, Manajemen, Bisnis dan Akuntansi, 2017)
Abstract: Textiles and clothing plays a major role in the development and industrialization process of countries and their integration into the world economy. In maintaining its customers to be loyal to their products, Giordano has been implementing two strategic approaches that are considered as two of its impactful weapons to stand out from the crowd of competition; those are brand equity and visual merchandising. The aim of this study is to analyze the effect of brand equity and visual merchandising on consumer purchase decision at Giordano Manado Town Square. The population of this study is the customer of Giordano Manado Town Square and the sample size is 100 respondents with the sampling method of convenience sampling. The finding of this study shows that brand equity and visual merchandising has an effect toward consumer purchase decision. So, related with the finding in this study, there are two recommendations for Giordano Manado Town Square, which are keep strengthen the value as a reputable brand by improving the product and services so that the expected value can reach the customer and keep offering and maintaining the creative display in the exterior and interior of the store.Keywords: brand equity, visual merchandising, consumer purchase decision